Fumigaclavine C ameliorates dextran sulfate sodium-induced murine experimental colitis via NLRP3 inflammasome inhibition - Wenjie Guo; Shasha Hu; Ahmed Elgehama; Fenli Shao; Ren Ren; Wen Liu; Wenjing Zhang; Xinlei Wang; Renxiang Tan; Qiang Xu; Yang Sun; Ruihua Jiao (Elsevier, 2015)
In the present study, the effect of Fumigaclavine C, a fungal metabolite, on murine experimental colitis induced by dextran sulfate sodium (DSS) and its possible mechanism were examined in vivo and vitro. Oral administration of Fumigaclavine C dose-dependently attenuated the loss of body weight and shortening of colon length induced by DSS. The disease activity index, histopathologic scores of musco was also significantly reduced by Fumigaclavine C treatment. Protein and mRNA levels of DSS-induced pro-inflammatory cytokines in colon, including TNF-α, IL-1β and IL-17A, were markedly suppressed by Fumigaclavine C. At the same time, decreased activation of caspase-1 in peritoneal macrophages was detected in Fumigaclavine C -treated mice which suggested that the NLRP3 inflammasome activation was suppressed. Furthermore, in the LPS plus ATP cell model, we found that Fumigaclavine C dose-dependent inhibited IL-1β release and caspase-1 activation. Taken together, our results demonstrate the ability of Fumigaclavine C to inhibit NLRP3 inflammasome activation and give some evidence for its potential use in the treatment of inflammatory bowel diseases.